Mecanismos de captação e toxicidade do metilmercúrio: Envolvimento do sistema glutamatérgico e do cálcio em fatias e mitocôndrias de ratos. - Roos, Daniel Henrique (2012)
Methylmercury (MeHg) is a highly toxic environmental contaminant that can be accumulated on several tissues, inducing cellular dysfunction on various organs, especially in the central nervous system (CNS). The mechanisms involved in the uptake, accumulation and toxicity of mercury (Hg) remain unclear. However, it has been suggested that the neurotoxicity mediated by MeHg induces changes in both glutamatergic system and calcium homeostasis. Indeed, the literature reports that calcium per se is able in inducing cellular damage. Thus, mercury and calcium can exert distinct or linked toxic effect that lead to mitochondrial and cellular dysfunction. The purpose of this study was to analyze the mechanisms of uptake and accumulation of mercury on liver slices exposed to MeHg or MeHg-Cysteine complex, as well as to compare the mitochondrial and cellular toxicity caused by both forms of MeHg. Moreover, this work examined the role of glutamatergic system on the toxicity mediated by MeHg in slices of cerebral cortex from rats and the effects of calcium exposure in mitochondria sustained with different energetic substrates. Our results showed that the mercury uptake was higher in the slices exposed to the MeHg-Cys complex that MeHg exposed slices. Indeed, the pretreatment with methionine (Met) (for 15 min.) reduced Hg uptake in liver slices. Likewise, mitochondria isolated of liver slices showed similar effect on Hg uptake. Parameters as free radical generation; oxygen consumption and mitochondrial function/Cell viability were more affected by MeHg-Cys complex than MeHg alone. Met pre-treatment was effective in preventing the MeHg or MeHg-Cys-induced toxicity in both liver slices and mitochondria. In cortical brain slices, the neurotoxicity induced by MeHg was verified only at higher concentration tested and after 2 or 5 hours of exposure. In addition, compounds that potentially modulate glutamatergic system (MK-801, guanosine, organo selenium compounds) were effective in preventing the MeHg-induced free radical generation. In mitochondria isolated from liver, Ca2+ caused an inhibition on the complex I activity; however, calcium did not alter the mitochondrial complex II activity. At low concentration, calcium exposure caused a small decrease in the mitochondrial membrane potential (ΔΨm) in Malate/Glutamate (Ma/Glu) and Succinate (Succ)-supported mitochondria. On the order hand, higher calcium levels were associated with a total ΔΨm loss in both Mal/Glu and Succ-oxidizing mitochondria. The mitochondrial redox state (NADP(H) and GSH pool) and oxygen consumption were extremely affected by calcium exposure only in Succ-supported mitochondria. Indeed, calcium caused an increase in free radical generation in mitochondria sustained with complex II substrate when compared to Mal/Glu-supported mitochondria. Taken together, our data collaborate to understanding the molecular mechanisms involved on the toxicology of mercury and calcium and consequently provide basis for further investigations on the role of Ca2+ and mercury in mitochondrial dysfunctions. In addition, the results obtained here may contribute to the discovery of new therapeutic agents capable of preventing or minimizing the damage induced by MeHg intoxication.